Spanish and Latin American women's crime fiction in the new millennium : from noir to gris - Vosburg, Nancy, 1953-; Molinaro, Nina L., 1960- (Cambridge Scholars Publishing, 2017)
"Crime fiction written by women in Spain and Latin America since the late 1980s has been successful in shifting attention to crimes often overlooked by their male counterparts, such as rape and sexual battery, domestic violence, child pornography, pederasty, and incest. In the twenty-first century, social, economic, and political issues, including institutional corruption, class inequality, criminalized oppression of immigrant women, crass capitalist market forces, and mediatized political and religious bodies, have at their core a gendered dimension. The conventions of the original noir, or novela negra, genre have evolved, such that some women authors challenge the noir formulas by foregrounding gender concerns while others imagine new models of crime fiction that depart drastically from the old paradigms. This volume, highlighting such evolution in the crime fiction genre, will be of interest to students, teachers, and scholars of crime fiction in Latin America and Spain, to those interested in crime fiction by women, and to readers familiar with the sub-genres of crime fiction, which include noir, the thriller, the police procedural, and the "cozy" novel."--Publisher